(untitled) - Williams, John A. (Boston, New York, 1997)
This volume presents primary source materials that illuminate the formation of the modern multiracial society of South Africa. Students will be enlightened by the "African Voices" that recur throughout the text, in the form of praise poems, trial testimonies, speeches, and manifestoes. Chronologies, maps, and lists of key terms and people enhance learning.
Keywords: Nam Phi; Lịch sử